Aristotle on prescription : deliberation and rule-making in Aristotle's practical philosophy - Alesse, Francesca (Philosophia antiqua, 2019)
The focus of Aristotle on Prescription is Aristotle's reflections on rule-making. It is widely believed that Aristotle was only concerned with decision-making, understood as a deliberative process enabling a person to arrive at particular, contingent decisions. However, rule-making is fundamental to Aristotle's ethical texts. Establishing rules means indicating patterns for action that are sufficiently specific to meet situational difficulties and sufficiently constant in time to provide us with a code of behaviour to be used in similar situations. When we prescribe rules, we demonstrate the ability to direct not only our own life but also other people's lives. Alesse's book explores Aristotle's deep reflections on the nature and functions of prescription, and on the relationship between rules and individual decisions.